Quantitative analysis of receptor allosterism and its implication for drug discovery - Zhang, Rumin (Henry Stewart Talks, 2015)
G protein-coupled receptors (GPCRs), Receptor agonism and allosterism, Orthosteric and allosteric binders, Inverse, partial and full agonists, Positive, silent and negative allosteric modulators (PAMs, SAMs and NAMs), Allosteric two-state model and general operational model with constitutive receptor activity, Optimal design of experiment, Global curve fitting analysis of affinity and efficacy parameters, Beta supremacy, Monte Carlo simulations